THE CARTESIAN ASPECTS OF SEMANTIC NATURALISM - Gilaitis, Mindaugas (Problemos, 2017)
The paper analyses theoretical presuppositions of the predominant form of semantic naturalism in contemporary analytic philosophy. The aim is to show that irrespective of the fact that the doctrine of semantic naturalism is grounded in ontological and epistemological naturalism, and is developed on the basis of semantic externalism, this conception of foundational semantics rests on internalist premises, and therefore should be construed as Cartesian. Theories and their interrelations that are assumed by semantic naturalism are explicated by relying on the tripartite interpretation of “the problem of intentionality”. The Cartesian aspects of the assumed theories – and thus of the form of semantic naturalism that is analysed – are then specified in the context of Hilary Putnam’s version of semantic externalism.
Keywords: semantic naturalism; theory of content; internalism; externalism; functionalism; representational theory of mind